Sistem Pendukung Keputusan Pemilihan Pegawai Terbaik Menggunakan Kombinasi Metode Pembobotan MEREC dan Simple Additive Weighting - Chandra, Iryanto; Hadad, Sitna Hajar (Forum Kerjasama Pendidikan Tinggi, 2024)
The selection of the best employees is an event that aims to appreciate and recognize the extraordinary performance of employees in a company. The implementation of the selection of the best employees is not without challenges and problems, one of the main problems is the risk of subjectivity in the assessment process, which can cause dissatisfaction among other employees if they feel that the assessment is unfair or transparent. The purpose of this study is to develop an SPK that can help in the selection of the best employees by using a combination of MEREC and SAW methods, a MEREC approach to manage and evaluate important criteria in employee selection, and integrate SAW as a mathematical method to provide weight and ranking candidates based on predetermined criteria. The recommendation for the results of the selection of the first best employee with a final SAW score of 0.8345 was obtained by Candidate 8, the second best employee with a final SAW score of 0.8253 was obtained by Candidate 6, and the third best employee with a final SAW score of 0.8068 was obtained by Candidate 3.